Nitrogen mineralization rate of winter cover crops in no-till system - Wamser, Anderson Fernando (2021)
A field experiment was carried out in Eldorado do Sul, RS, Brazil, on a Rhodic Paleodult soil, in2001, with the objective of evaluating the N release of different winter cover crop systems (winter fallow, black oat, common vetch, radish, black oat+common vetch, black oat+radish, common vetch+radish, blackoat+radish+common vetch) during the initial development of maize. The N supply was estimated by using decomposition bags filled with samples of the cover crops, and by analysing the level of mineral N in the soil. The use of common vetch and radish, in contrast of black oat, provided superior release of N during the first 58 days of decomposition, resulting in the highest soil N-NO3– levels.